2007
DOI: 10.1017/s0021859607006922
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on sugarbeet yield in the UK: 1976–2004

Abstract: SU MMARYSince the 1970s, the delivered sugar yield per hectare has risen at an average annual rate of 0 . 111 t/ha, while the sugar yield in the official variety trials has increased at an average annual rate of 0 . 204 t/ha. These increases are usually considered to be the result of improvements in varieties and in beet agronomy. The present paper considers the possible impact of recent changes in climate on UK sugar yields by using the Broom's Barn Crop Growth Model and daily weather data collected over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…3). These results are consistent with previous work that has found long-term climate trends should have increased sugar beet yields in the United Kingdom, decreased wheat yields in France, and that the yield potential of wheat and barley has declined over much of Europe due to warming (3,9,16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). These results are consistent with previous work that has found long-term climate trends should have increased sugar beet yields in the United Kingdom, decreased wheat yields in France, and that the yield potential of wheat and barley has declined over much of Europe due to warming (3,9,16).…”
Section: Discussionsupporting
confidence: 92%
“…Existing empirical evidence for either explanation is typically weak, taking the form of coincidence in the direction and timing of expected climate or policy effects with yield trends, so the relative importance of these mechanisms has not been rigorously demonstrated (3,9). More persuasive detection and attribution studies instead identify impacts using a distinctive spatial pattern of trends associated with climate change forcing (10,11).…”
mentioning
confidence: 99%
“…Technological advances might also indirectly result from climate change, such as improved varieties that allow for earlier sowing dates. Effects of climate and technological advances on annual yield rates are closely related but can be separated using data from variety trials, as demonstrated by Jaggard et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increasing fear how the future climate conditions may affect the productivity of crops (LUO et al, 2005;JAGGARD et al, 2007;COSTA et al, 2009). Among these futures climate conditions are the increase of CO2 concentration and alteration on the water availability (LUO et al, 2005;JAGGARD et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among these futures climate conditions are the increase of CO2 concentration and alteration on the water availability (LUO et al, 2005;JAGGARD et al, 2007).…”
Section: Introductionmentioning
confidence: 99%